Rapid tumor DNA analysis of cerebrospinal fluid accelerates treatment of central nervous system lymphoma - Gupta, Mihir; Bradley, Joseph D.; Massaad, Elie; Burns, Evan J.; Georgantas, N. Zeke; Maron, Garrett E.; Batten, Julie M.; Gallagher, Aidan; Thierauf, Julia; Nayyar, Naema; Gordon, Amanda; Jones, SooAe S.; et al. (Blood, 2024)
Delays and risks associated with neurosurgical biopsies preclude timely diagnosis and treatment of central nervous system (CNS) lymphoma and other CNS neoplasms. We prospectively integrated targeted rapid genotyping of cerebrospinal fluid (CSF) into the evaluation of 70 patients with CNS lesions of unknown cause. Participants underwent genotyping of CSF-derived DNA using a quantitative polymerase chain reaction-based approach for parallel detection of single-nucleotide variants in the MYD88, TERT promoter, IDH1, IDH2, BRAF, and H3F3A genes within 80 minutes of sample acquisition. Canonical mutations were detected in 42% of patients with neoplasms, including cases of primary and secondary CNS lymphoma, glioblastoma, IDH-mutant brainstem glioma, and H3K27M-mutant diffuse midline glioma. Genotyping results eliminated the need for surgical biopsies in 7 of 33 cases (21.2%) of newly diagnosed neoplasms, resulting in significantly accelerated initiation of disease-directed treatment (median, 3 vs 12 days; P = .027). This assay was then implemented in a Clinical Laboratory Improvement Amendments environment, with 2-day median turnaround for diagnosis of CNS lymphoma from 66 patients across 4 clinical sites. Our study prospectively demonstrates that targeted rapid CSF genotyping influences oncologic management for suspected CNS tumors.
Online verfügbar: 24. Mai 2024
Gesehen am 06.03.2025